Fuzzy super twist sliding mode control strategy for permanent magnet synchronous motor. (15th June 2022) - Zhou, Kai; Wang, Hanfeng; Sun, Dongyang; Jin, Ningzhi
To improve the dynamic quality of permanent magnet synchronous motor (PMSM) speed control system, a sliding mode control strategy based on a fuzzy super twist algorithm (STA-SMC) is proposed to solve the chattering problem of the traditional sliding mode control strategy. The traditional sliding mode control (SMC) in the speed controller is replaced by the STA-SMC, which is a second-order sliding mode control. The chattering of the SMC can be effectively suppressed, and the robustness of the system can be improved. The fuzzy controller is used to adjust the control parameters of the STA-SMC, bringing them into alignment with fuzzy rules to effectuate the self-tuning process of the super twist algorithm sliding mode, so as to accelerate the convergence speed of the system and improve the steady-state and dynamic characteristics of the system. Through simulation and experiments, the effectiveness and feasibility of the control strategy are demonstrated in this paper.